Islamic Organizations and Societal Development: An Examination of Kiai Soedja's Perspectives on Establishing Penolong Kesengsaraan Oemoem (PKO) Muhammadijah - Iskandar Iskandar; Aan Andriawan; Fani Nur Dwi Saputro; Dwi Miftakhul Huda (KURAS Institute, 2025)
The urgency of this research is to see the impact of the results of Kiai Soedja's thoughts on society today in the fields of health, social, and economy. This can be seen by the development of Muhammadiyah social institutions that are developing today starting from the establishment of the PKO business charity which was the idea of Kiai Soedja'. The research method used is the historical research method. The stages involved in the method are topic selection, heuristics, verification, interpretation, and historiography. The results showed that PKO was born from the idea of Kiai Soedja', whose thoughts surpassed the thoughts of Muhammadiyah members at that time. Kiai Soedja' was able to initiate the construction of poor houses, hospitals, and orphanages in only 11 years. The PKO Poor House was estabilished on 13 January 1923, the PKO Remsi Hospital was established on 15 February 1923, and the PKO Orphanage was inaugurated on 5 October 1931, even though the poor house had actually existed since 1923. After conducting research, it can be concluded that Kiai Soedja' is a figure who is able to break the view of limitations. He was able to pioneer the development of social activities in Muhammadiyah with the PKO Charity. This research is useful for the development of local history and introducing an important figure in the history of health in Indonesia.